Solvo-thermal synthesis of an ultra-stable 3D luminescent zinc(II) coordination material and its application as a bi-functional re-generable visual fluorescent probe for Nicotinamide and Tetraphenylboron anion. (August 2019) - Ji, Song Jie; Ma, Wen; Li, Xin Shu; An, Jun Dan; Zhang, Hui Min; Li, Yong; Du, Gui Xiang; Fei, Ling; Lacoste, Jed D.; Liu, Jun Jie; Wu, Xiang Xia; Liu, Yuan Yuan; et al.
Abstract: During the past two decades, metal-organic frameworks (MOFs) have received significant interest because these materials possess beautiful structural motifs and unique applications. Light-emitting MOFs sensors are favorable because these materials have large surface area and excellent framework stability, which can differentiate analytical objects for applications toward environmental protection, homeland security and human health. In this work, under the powerful solvo-thermal conditions, a bi-functional ligand with large conjugated biphenyl aromatic backbones has been used to prepare the unique ultra-stable three-dimensional(3D) luminescent zinc(II) coordination compound [Zn2 ( μ 5 -L)( μ 3 -OH)(H2 O)2 ]·(0.75DMAC)n (1 ) (DMAC = Dimethylacetamide). In 1, these penta-coordinated L 3− ligands and the bridging ligand μ 3 -OH link together with these neighboring zinc(II) centers, which ultimately constructs the 3D nano-porous coordination material of 1 . 1D rhombic channel with a corresponding edge distance of 12.167(6) Å × 10.912(1) Å can be found between central metal(II) vertices along the crystallographic b axis. The calculation using the PLATON program shows the total solvent area is 581.7 Å 3, which occupies 25.2% of the unit cell's volume (2306.9 Å 3 ). Powder X-ray diffraction (PXRD) pattern has been performed confirming the purity of these bulky samples 1 . It is worth noting that 1 shows excellent chemical stability, which can maintain structural integrity not only in various solvents but also aqueous environments with pH varying from 2 to 12. Photo-luminescent measurements show that 1 can perform highly sensitive and real-time chemical sensing of nicotinamide with good reusability, high Ksv quenching efficiency (2.24 × 10 4 M −1 ) and low detection limit values (0.14 μM). Meanwhile 1 also shows visual photo-luminescent detection of tetraphenylboron (BPh4 -, Ph = phenyl) anion in aqueous solutions with high Ksv quenching efficiency (1.16 × 10 5 M −1 ) and low detection limit values (0.028 μM). To the best of our knowledge, 1 presents the first example of an ultra-stable 3D zinc(II) nano-porous metal organic material as the bi-functional re-generable luminescent probe for nicotinamide and tetraphenylboron. Graphical abstract: Image 1 Highlights: An ultra-stable 3D zinc(II) coordination polymer (1 ) is prepared under solvo-thermal conditions. 1 shows excellent chemical stability. 1 performs real-time chemical sensing of nicotinamide with good reusability and high quenching efficiency. 1 can be applied as the re-generable visual luminescent probe for tetraphenylboron.